Psychological Features of Inter-ethnic Relations From the Perspective of Tolerance - Kykhtiuk, Oksana (Psychological Prospects Journal, 2014)
The article highlights the main aspects of inter-ethnic relations through the prism of perception of student youth of other nationalities. The theoretical and empirical study of the problem of the ethnic person’s tolerance was carried out through the discourse of the concepts of the ethnic stereotype, attitude, prejudice, social distance, the ethnic tolerance, ethnically tolerant person.There were considered the psychological peculiarities of the adolescence, determined the main difficulties of the successful formation and self-realization of youth. The concepts of general and ethnic tolerance, social and ethnic stereotypes, social perception, prejudice, social representations, social distance were analyzed. There were substantiated the mai psychological causes of the intolerance appearance, prejudices towards theother social groups, in particular, to the ethnic minorities and nationalities, degress of social distance of student youth in the process of the inter-ethnic cooperation. The paper contains the data related to general, social, and ethnic tolerance, mean indices of tolerance among the students which were manifested by tolerant or intolerant behavior reactions. The results of the research show that the maximal social distance of the student youth was caused by negative ethnic stereotypes and insufficiency of ethnically tolerant personality qualities. By contrast, the minimal social distance between young people was caused by a sufficient bulk of information concerning a certain nationality, ethnicity, lack of negative ethnic stereotypes, and attitudes.
Keywords: social distance, social perception, social expansiveness, social and ethnic stereotypes, social representation, tolerance, ethnically tolerant person.